Peran Pendidikan Agama Islam dalam Membentuk Kepribadian di Era Disrupsi - Samsudin Samsudin (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
Along the nun of year 2000 epoch progressively go forward. The progress bring big impact in human life. Do not all impact change of that epoch of goodness but also there is ugly. So that as generation router of nation have to can filter the impact rampant. Criminality action progressively, downhill nation moral progressively. For that, very required by weapon to decrease the mentioned. Many people which its personality concern. Many people which its personality concern. They understand law, but they also a lot impinge it. When wishing something select; choose by which instan do not want to strive.Education of Islam as one ofthe stock to follow motion progress of epoch so that forming of taft person. Personality everybody do not goodness, depended from its factors, especially environment ugly. Someone either or behaviour always become focus in society sophisticated. Technological progressively, many people imitating behaviour of public media. Education of Islam can form good moslem person can face multivariously of manner change of epoch. By having education of allocation Islam change of epoch can as medium to become sophisticated human being and water down life.